Digital Governance and the AUPB: A Legal Analysis of the Implementation of the SIPD in Raja Ampat - Fenita Malendes; Dwi Pratiwi Markus; Anggun Kirana (Fakultas Hukum Universitas Muhammadiyah Sorong, 2026)
This study aims to analyze the implementation of the Local Government Information System (SIPD) in local financial management in Raja Ampat Regency. The method used is an empirical-juridical approach, analyzing the relationship between the legal norms governing the SIPD and the reality of its implementation in the field. The novelty of this study compared to previous research lies in the analysis of the implementation of the Local Government Information System (SIPD) in the Raja Ampat archipelago using the Principles of Good Governance (AUPB) as an evaluation framework within the study of administrative law. The findings indicate that although the Raja Ampat Regency Government has fulfilled its normative obligations in implementing the SIPD across the entire cycle of regional financial planning and management, the effectiveness of its implementation remains hindered by limited internet connectivity, national server disruptions, low human resource capacity, and resistance to digital transformation factors that collectively result in a significant deviation between “law in the books” and “law in action.” The AUPB analysis reveals that the principles of legal certainty, accuracy, efficiency, effectiveness, transparency, and justice have not been optimally fulfilled. The conclusion of this study emphasizes the need for policies that are more adaptive to the geographical characteristics and institutional capacities of island regions, including the strengthening of digital infrastructure and the continuous improvement of civil servants’ technical competencies.